2006
DOI: 10.1021/ja0632106
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis of Diribonucleoside Monophosphate Cleavage by Water Soluble Copper(II) Complexes of Calix[4]arene Based Nitrogen Ligands

Abstract: Calix[4]arenes functionalized at the 1,2-, 1,3-, and 1,2,3-positions of the upper rim with [12]ane-N(3) ligating units were synthesized, and their bi- and trimetallic zinc(II) and copper(II) complexes were investigated as catalysts in the cleavage of phosphodiesters as RNA models. The results of comparative kinetic studies using monometallic controls indicate that the subunits of all of the zinc(II) complexes and of the 1,3-distal bimetallic copper(II) complex 7-Cu(2) act as essentially independent monometalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 32 publications
1
63
2
Order By: Relevance
“…In the cleavage of HPNP (water, pH 7, 258C), cooperation between metal centres is significant in the 1,2-vicinal dinuclear complex 37-Cu 2 with a . 10 3 rate enhancement at 0.2 mM catalyst over the reaction carried out in the presence of buffer alone, and 42-fold and 73-fold accelerations over 35-Cu and [12]aneN 3 -Cu, respectively (31). In contrast, the catalytic efficiency of 1,3-distal bimetallic regioisomer 38-Cu 2 is about twice as great as that of monometallic Trimetallic complex 39-Cu 3 cleaves a series of diribonucleoside monophosphates (UpU, UpG, GpU, GpG, ApG, CpG, GpA and CpA) with catalytic rate accelerations in the order of 10 4 -fold in most cases (31).…”
Section: -Mmentioning
confidence: 94%
See 1 more Smart Citation
“…In the cleavage of HPNP (water, pH 7, 258C), cooperation between metal centres is significant in the 1,2-vicinal dinuclear complex 37-Cu 2 with a . 10 3 rate enhancement at 0.2 mM catalyst over the reaction carried out in the presence of buffer alone, and 42-fold and 73-fold accelerations over 35-Cu and [12]aneN 3 -Cu, respectively (31). In contrast, the catalytic efficiency of 1,3-distal bimetallic regioisomer 38-Cu 2 is about twice as great as that of monometallic Trimetallic complex 39-Cu 3 cleaves a series of diribonucleoside monophosphates (UpU, UpG, GpU, GpG, ApG, CpG, GpA and CpA) with catalytic rate accelerations in the order of 10 4 -fold in most cases (31).…”
Section: -Mmentioning
confidence: 94%
“…10 3 rate enhancement at 0.2 mM catalyst over the reaction carried out in the presence of buffer alone, and 42-fold and 73-fold accelerations over 35-Cu and [12]aneN 3 -Cu, respectively (31). In contrast, the catalytic efficiency of 1,3-distal bimetallic regioisomer 38-Cu 2 is about twice as great as that of monometallic Trimetallic complex 39-Cu 3 cleaves a series of diribonucleoside monophosphates (UpU, UpG, GpU, GpG, ApG, CpG, GpA and CpA) with catalytic rate accelerations in the order of 10 4 -fold in most cases (31). Rate enhancements rise to 10 5 -fold in the cleavage of UpU and UpG and this is believed to be caused by the additional binding site arising from the copper-assisted deprotonation of the uracil moiety at the 5 0 -terminus.…”
Section: -Mmentioning
confidence: 94%
“…The high catalytic efficiency was therefore said to arise from the dynamic binding of the substrate and the "pre-transition state", which was made possible by "rapid, low energy conformational changes of the flexible calix [4]arene backbone". Later work indicated that an eclipsed arrangement of the metals was optimum [66]. As can be seen in Figure 8, the catalyst likely flexes through structures that, first, complement (and facilitate) di-Cu binding by the phosphate and, then, secondly, complement (and faciltate) the transition state for the hydrolysis reaction.…”
Section: Phosphate Ester Hydrolysis Catalystsmentioning
confidence: 98%
“…In the aim at developing metal catalysts which are soluble enough in water to avoid the use of organic cosolvents, the [12]aneN 3 ligating unit seemed appropriate, because its high affi nity for zinc(II) in water (Log K = 8.4 at 25 ° C) ensures extensive binding of the metal ion to the ligand even at submillimolar concentrations. 32 Unfortunately, the zinc(II) complexes of ligands 28 -31 were not soluble enough in water for catalytic studies. Furthermore, catalytic studies carried out in 50% aqueous CH 3 CN (Table 8.3 ) revealed a disappointing lack of synergism between metal ions, which is at variance with the results obtained with the corresponding BAMP complexes.…”
Section: Artifi Cial Nucleases: Zinc(ii) Complexesmentioning
confidence: 99%